ANALISIS BUDAYA DAN PRODUKTIVITAS KERJA PETANI PLASMA PADA PERKEBUNAN KELAPA SAWIT (STUDI KASUS PADA PT. SULTRA PRIMA LESTARI) - Khan, Syahrul; Nalefo, La; Arif, La Ode Kasno (Universitas Halu Oleo, 2024)
This study aims to determine the work culture and work productivity of plasma farmers working at PT Sultra Prima Lestari and the relationship between the two. The population of this study is all plasma farmers who work at PT Sultra Prima Lestari in Andowia District, North Konawe Regency, totaling 120 people divided into 10 farmer groups. Determination of the number of research samples using the Slovin formula with an error rate of 25%, so that the research sample amounted to 54 respondents. This research uses a quantitative approach. The sampling technique used a proportional random sampling technique. Data collection in the field using survey methods, interviews, and documentation using instruments in the form of questionnaires or questionnaires. Variables in this study, namely the work culture of farmers (variable X) and work productivity of farmers (variable Y). The data were analyzed in a quantitative descriptive way using the class interval formula and the Spearman rank correlation formula with the help of SPSS 26 software. The results showed that the work culture of plasma farmers included togetherness, and work intensity in the production of oil palm farming at PT Sultra Perima Lestari was in the high category. The work productivity of plasma farmers includes quality of work, quantity of work, and timeliness of work in the production of oil palm farming at PT Sultra Perima Lestari is in the high category. Work culture with plasma farmers' work productivity has a significant relationship with a value of 0.491 ≥ r table 0.26, meaning it is quite close and the sig value of 0.00 is smaller than the significance level at the α level of 0.05.